Hadis dan Legitimasi Kekuasaan: Kritik Asma Afsaruddin terhadap Otoritarianisme Politik (Kajian Hermeneutika Historis Islam Kontemporer) - Nuryanto (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2026)
This article examines Asma Afsaruddin’s critique of the instrumentalization of hadith as a theological device for legitimizing political authoritarianism in Islamic history. Throughout the medieval and modern periods, despotic rulers have appropriated traditions enjoining absolute obedience to the ruler most conspicuously the tradition of Hudhayfah ibn al-Yaman recorded in Sahih Muslim to silence dissent and sacralize tyranny. Employing a qualitative library-research design with a diachronic-hermeneutical approach, this study analyzes Afsaruddin’s principal works and confronts them with the classical corpus of obedience traditions and their medieval commentaries. The findings demonstrate that Afsaruddin reconstructs a semantic genealogy in which the concepts of taʼah (obedience) and jamaʼah (community) were transformed from conditional, contractual, and ethically bounded notions in the formative period into instruments of unconditional submission engineered by dynastic court scholarship. Afsaruddin retrieves the suppressed counter-memory of the early community like grounded in election, consultation (shura), moral excellence (fadilah), and the duty of commanding right as evidence that rejecting an unjust ruler is consonant with, rather than contrary to, normative Islam. The article concludes that her historical hermeneutics furnishes an accountable, inclusive, and anti-authoritarian political theology for contemporary Muslim societies.